2015
DOI: 10.3892/mmr.2015.3796
|View full text |Cite
|
Sign up to set email alerts
|

Continuous expression of CD83 on activated human CD4+ T cells is correlated with their differentiation into induced regulatory T cells

Abstract: CD83 is a widely recognized surface marker for mature dendritic cells, which are essential for priming naïve CD4+ T cells into effector cells. However, CD83 is also expressed on activated CD4+ T cells, which remains an enigma in T-cell mediated immunity. Therefore, the identification of the biological features and regulation of the expression of CD83 on activated CD4+ T cells is important in understanding the function of CD83 in the adaptive immune response. The present study revealed a time-dependent manner o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…These murine data are further supported by studies in the human system, which also showed a distinct CD83 expression profile comparing anti-CD3/CD28-stimulated human effector versus regulatory T cells (23,37). Upon TCR-stimulation in vitro, human CD4 + T cells upregulate CD83 expression transiently with a maximum expression at day 2 followed by a strong decline after day 3 (37). By contrast, expanded human CD25 hi CD45RA + Tregs already reached their CD83 mRNA expression maximum 3 h after stimulation (23).…”
Section: Treg Differentiation and Stabilitymentioning
confidence: 61%
See 2 more Smart Citations
“…These murine data are further supported by studies in the human system, which also showed a distinct CD83 expression profile comparing anti-CD3/CD28-stimulated human effector versus regulatory T cells (23,37). Upon TCR-stimulation in vitro, human CD4 + T cells upregulate CD83 expression transiently with a maximum expression at day 2 followed by a strong decline after day 3 (37). By contrast, expanded human CD25 hi CD45RA + Tregs already reached their CD83 mRNA expression maximum 3 h after stimulation (23).…”
Section: Treg Differentiation and Stabilitymentioning
confidence: 61%
“…By contrast, expanded human CD25 hi CD45RA + Tregs already reached their CD83 mRNA expression maximum 3 h after stimulation (23). Strikingly, TCRstimulation of human and murine CD4 + T cells together with transforming growth factor beta (TGFβ) not only resulted in the expected differentiation into CD4 + CD25 + Foxp3 + iTregs but also in a sustained and stable CD83 expression (37,38). In addition, immunofluorescence microscopy revealed CD83 to colocalize with CD25 on those cells (37).…”
Section: Treg Differentiation and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…CD83 was first described for Langerhans cells and activated lymphocytes. It is a conserved member of the immunoglobulin superfamily and is also known as one of the most characteristic cell surface markers for fully mature DCs in peripheral circulation (31,50,51). Although CD83 plays essential roles in both the central and peripheral immune systems, the underlying mechanisms by which CD83 regulates immune responses remain enigmatic.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is induced on activated human B cells (12,13), monocytes (14), macrophages (14), neutrophils (15), and a regulatory subset of NK cells (16). We and others described CD83 on activated human T cells (6,10,17), but its expression on specific T cell subsets has not been well scrutinized (18).…”
mentioning
confidence: 99%